function notation algebra 1

Algebra
Tutor: None Selected Time limit: 1 Day

How do I rewrite this equation as function notation? 

3x + 3y = 6

Feb 7th, 2015

3y=-3x+6

f(x)=-3x/3+6/3

f(x)=-x+2

Feb 7th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Feb 7th, 2015
...
Feb 7th, 2015
Dec 7th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer